Pengaruh Orientasi Pasar, Pembelajaran Organisasi Terhadap Keunggulan Bersaing Dalam Meningkatkan Kinerja Pemasaran (Tinjauan Teoritis) - Aris Mardiyono (FEB UNTAG Semarang, 2015)
AbstractCompetitive advantage can be achieved if the company has the ability to deliver more value to customers than its competitors. Competitive advantage comes from a variety of corporate activities consisting of designing, manufacturing, marketing, shipping, and product sales. The purpose of the study analyzed the effect of market orientation, organizational learning on competitive advantage in improving marketing performance. Five hypotheses are proposed, among others, There are positive and significant impacts of market orientation, organizational learning on competitive advantage.And there is a positive and significant influence of market orientation, competitive advantage, organizational learning on marketing performance.Keyword: Market Orientation, Organizational Learning, Competitive Advantage, Performance Marketing